Kontranarasi Ekstrimisme di Ruang Digital: Strategi Pendampingan Peningkatan Agensi Nalar Moderasi Beragama pada Fatayat NU Sumenep - Samheri; Fathurrosyid; Fairuzah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Extremism in the digital space continues to grow through narratives that lead to radicalization, necessitating effective strategies for building counter-narratives based on religious moderation. This study aims to identify and develop mentoring strategies for Fatayat NU Sumenep to enhance their agency in promoting religious moderation reasoning in the digital space. Using a qualitative approach, this research employed Focus Group Discussions (FGDs) involving members and leaders of Fatayat NU Sumenep to explore their experiences, understanding, and needs in confronting extremist narratives. The findings indicate that increasing digital literacy, strengthening critical capacity in assessing religious content, and collaborating with various stakeholders are strategic steps in constructing effective counter-narratives. With the right strategies, Fatayat NU Sumenep can become key agents in disseminating moderate Islamic values and countering extremism in the digital space.